The pattern of increasing intraocular pressure after phakic anterior chamber intraocular Lens Implantation - Puty Lestari; Widyandana Widyandana; Agus Supartoto (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2017)
Background: Phakic intraocular lenses (IOL) are being used to correct refractive errors. We studied the pattern of increasing Intraocular Pressure (IOP) after Phakic Anterior chamber intraocular lens implantation as the risk after surgery. Methods: Sixty eyes of 30 patients were enrolled. All eyes underwent the same protocol with IOP examination before surgical procedure, and during follow up (one day after, 2 weeks, 1 month, 2 months and 3 months) after implantation of phakic IOL anterior chamber. All results were analyzed statistically using SPSS 16 statistics software. Correlation between parameter were analyzed using the wilcoxon test. Results: Median IOP before surgery were 14.00 mmHg (IOP), during follow up 17.00 mmHg (IOP I), 16.00 mmHg (IOP II) , 17.00 mmHg (IOP III), 15.00 mmHg (IOP IV), 15.00 mmHg (IOP V). The increasing of IOP between pre surgery and follow up a day after was found to correlate significantly (p=0.03), there were increasing of IOP after 2 weeks, a month, 2 and 3 months but no significant difference. Conclusion: There were significant of increasing IOP before surgery compare to a day after surgery,then the pattern of increasing IOP tend to be stable. There were no significant increasing of IOP during 3 months follow up.